2010
DOI: 10.4314/sjms.v4i4.51005
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cytomegalovirus among blood donors and antenatal women attending two hospitals in Khartoum State

Abstract: Back ground: Cytomeglovirus(CMV) is a common viral infection globally. Although most infections are subclinical; infection during pregnancy may be associated with serious outcome such as abortion, stillbirth and congenitally malformed child. Methods and results: During the period from June to July2003, 250 subjects (150 blood donors and 100 women presenting to Khartoum Teaching Hospital's and Omdurman Maternity Hospital respectively)had their blood tested for IgG antibodies against Cytomegalovirus using ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…The estimated seroprevalence of CMV IgM was high, indicating the likelihood of an endemic nature of infection in the Suez Canal Area of Egypt, and confirmed the ubiquitous past exposure to infection in the Suez Canal area. Our results also confirmed data of previous studies from Egypt and other Middle Eastern countries [ 3 , 6 , 14 , 15 ]. In a study from Iran by Bagheri et al [ 3 ], the majority of pregnant women (72.1%) were positive for CMV IgG and 2.5% were positive for CMV IgM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The estimated seroprevalence of CMV IgM was high, indicating the likelihood of an endemic nature of infection in the Suez Canal Area of Egypt, and confirmed the ubiquitous past exposure to infection in the Suez Canal area. Our results also confirmed data of previous studies from Egypt and other Middle Eastern countries [ 3 , 6 , 14 , 15 ]. In a study from Iran by Bagheri et al [ 3 ], the majority of pregnant women (72.1%) were positive for CMV IgG and 2.5% were positive for CMV IgM.…”
Section: Discussionsupporting
confidence: 93%
“…In a study in Egypt [ 14 ], there were no cases of primary CMV diagnosed in 132 pregnant women, and only 4.5% of these women were diagnosed with recurrent CMV infection, which was defined as being IgG positive prior to pregnancy, IgG positive at the first pregnancy visit without IgM test, or IgM positive with high IgG avidity. In Sudan [ 15 ], it was reported that CMV seroprevalence among antenatal women was 84%.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study susceptibility was lower than that reported for France [31], Nepal [32], India [13], [33], [34], Switzerland [35], Croatia [36], Malaysia [37], Iran [12], [38], Poland [39], Ireland [10], Russia [40], Taiwan [41], Germany [42], Azerbaijan [43], Bangladesh [44], and Brazil [45]. In comparison to Arab countries, this study susceptibility rate was lower to that reported for Egypt [46], Sudan [47], Syria [48], and Jordan [15], but similar to that reported for Saudi Arabia [49], and higher to rate in Qatar [50], Sudan [51], and Tunisia [52].…”
Section: Discussionsupporting
confidence: 67%
“…The results of our study were generally consistent with those of other reports from developing countries where HCMV infection occurs particularly in immune-compromised individuals. [23][24][25][26][27] We therefore report for the first time in Nigeria, a study evaluating the prevalence of HCMV infection by qualitative PCR in HIV infected patients.…”
Section: Discussionmentioning
confidence: 99%